2013
DOI: 10.1371/journal.pone.0062402
|View full text |Cite
|
Sign up to set email alerts
|

Tau Passive Immunotherapy in Mutant P301L Mice: Antibody Affinity versus Specificity

Abstract: The use of antibodies to treat neurodegenerative diseases has undergone rapid development in the past decade. To date, immunotherapeutic approaches to Alzheimer’s disease have mostly targeted amyloid beta as it is a secreted protein that can be found in plasma and CSF and is consequently accessible to circulating antibodies. Few recent publications have suggested the utility of treatment of tau pathology with monoclonal antibodies to tau. Our laboratory has begun a systematic study of different classes of tau … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
122
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(126 citation statements)
references
References 29 publications
3
122
1
Order By: Relevance
“…While studies have traditionally focused on targeting A␤ to prevent and treat AD, more research is now being dedicated to tau. However, most of the studies conducted using tau passive immunotherapy have targeted phosphorylated tau species known to be present in the late stages of aggregation and have resulted in a decrease of NFTs [35][36][37]. While NFTs have historically been the main tau species of interest, more results are emerging to suggest that toxicity and neuronal loss exceeds and occurs prior to NFT accumulation [1][2][3][4][5][6], thereby implicating the importance of intermediate tau species in toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While studies have traditionally focused on targeting A␤ to prevent and treat AD, more research is now being dedicated to tau. However, most of the studies conducted using tau passive immunotherapy have targeted phosphorylated tau species known to be present in the late stages of aggregation and have resulted in a decrease of NFTs [35][36][37]. While NFTs have historically been the main tau species of interest, more results are emerging to suggest that toxicity and neuronal loss exceeds and occurs prior to NFT accumulation [1][2][3][4][5][6], thereby implicating the importance of intermediate tau species in toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in order to stop the initial toxicity and the spread of disease, tau oligomers may be the best target. Moreover, it was recently shown that antibodies confer beneficial effects by targeting tau found extracellularly, implying that antibodies do not need to enter cells in order to reduce the toxic effects of tau, but may instead target tau which may be involved in the propagation of pathology [37,51]. Additionally, studies of tau therapeutics for neurodegenerative disease have primarily used transgenic mouse models expressing mutant tau.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2), or by blocking neuronal uptake of the protein [143]. Passive immunization with antiphospho-tau antibodies reduce tau pathology and functional deficits [137,[144][145][146], and antibodies targeting tau oligomers have also shown promise in transgenic models [136,147], including a concomitant upstream reduction in Aβ pathology [148]. In this sense, there are 3 anti-tau antibodies currently being studied in phase I trials (Table 1).…”
Section: Immunotherapy Targeting Taumentioning
confidence: 99%
“…42,43 Briefly, the brain was removed and divided at the midline so that just one half of brain was dissected for biochemical analysis. Forebrain and hindbrain were homogenized separately using an appropriate volume of homogenizing buffer, a solution of TBS, pH 7.4, containing 10 mM sodium fluoride, 1 mM sodium vanadate and 2 mM EGTA, plus a complete Mini protease inhibitor cocktail (Roche, Branford, CT, USA).…”
Section: Immunohistochemistrymentioning
confidence: 99%